"NGGADUNG" VISUALIZATION OF THE DEDICATION OF THE NGAGLIK COMMUNITY THROUGH DRAMATIC DANCE IN THE PROCESSING OF GADUNG TUBERS - AMADENTA, OBY; Dwi Sasanadjati, Jajuk (Solah, 2025)
The dance work "Nggadung" was inspired by the dedication of the people of Ngaglik Hamlet, Kediri, in processing gadung tubers into chips. Gadung tubers, which contain natural toxins, require special skills and careful processing stages to be safe to consume. Through the choreographer’s empirical experience and direct observation of the processing process, this work presents a visualization of cultural values in the form of precision, hard work, and mutual cooperation of the Ngaglik community in the form of dramatic dance. The process of creating works uses Jacqueline Smith’s construction method approach I I, with stages of exploration, improvisation, evaluation, and the formation of motion motifs that describe the process of "nggadung" in a representative-symbolic manner. This work involves 7 dancers with the use of distinctive properties, natural makeup, and clothing in shades of gray and white as a symbol of the gadung processing process. The results show that the transformation of the process of processing gadung tubers into a form of performing art is able to become an educational and reflective medium for local wisdom. In conclusion, the "Nggadung" dance not only displays aesthetic beauty, but also functions as an effort to preserve culture and strengthen community identity through visualization of the value of dedication in daily life practices.